2011
DOI: 10.1007/978-1-61779-458-2_27
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 and the Septohippocampal System: Intrinsic Actions and Autoimmune Processes Relevant to Neuropsychiatric Disorders

Abstract: The effects of IL-2 on brain development, function, and disease are the result of IL-2's actions in the peripheral immune system and its intrinsic actions in the central nervous system (CNS). Determining whether, and under what circumstances (e.g., development, acute injury), these different actions of IL-2 are operative in the brain is essential to make significant advances in understanding the multifaceted affects of IL-2 on CNS function and disease, including psychiatric disorders. For several decades, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Therefore, there may exist close relationship between the IL-2, dopaminergic dysfunction and TD symptom in schizophrenia patients. Furthermore, IL-2 could lead to the autoimmune responses of neurons (Petitto et al, 2012a) and subsequently affect neuronal function and produce neuroinflammation (Song et al, 1999). For example, (McAfoose andBaune, 2009) and(de Araujo et al, 2009) reported that IL-2 increased survival and synaptogenesis of dopaminergic neurons during development.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, there may exist close relationship between the IL-2, dopaminergic dysfunction and TD symptom in schizophrenia patients. Furthermore, IL-2 could lead to the autoimmune responses of neurons (Petitto et al, 2012a) and subsequently affect neuronal function and produce neuroinflammation (Song et al, 1999). For example, (McAfoose andBaune, 2009) and(de Araujo et al, 2009) reported that IL-2 increased survival and synaptogenesis of dopaminergic neurons during development.…”
Section: Discussionmentioning
confidence: 98%
“…Ancillary to the primary purpose, it found also that serum BDNF was elevated significantly in the ASD patients compared with healthy controls. Several brain disorders, associated with alterations of the normal mechanisms controlling development, have been associated with specific variants of cytokines and/or their receptors (Angelidou et al 2012;Petitto et al 2012;Vezzani and Friedman 2011). Cytokines may originate from peripheral immune cells and reach the CNS by crossing the blood-brain barrier or may be produced directly within the CNS by neurons and glial cells.…”
mentioning
confidence: 99%
“…20 Many studies have shown that people with neuropsychiatric illnesses have impaired peripheral immune systems, and there is currently a lot of knowledge on the involvement of cytokines in brain processes. 21 There was a significantly lower IL-10 blood level in children with ADHD compared to the normal controls. A previous study by Cortese et al, 2019, 22 showed a significant negative correlation between IL-10 and ADHD symptoms.…”
Section: Discussionmentioning
confidence: 86%